1988
DOI: 10.1001/jama.1988.03410020067030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Acyclovir Suppression of Frequently Recurring Genital Herpes Simplex Virus Infection

Abstract: Normal adults with six or more episodes of genital herpes in the previous year were enrolled in a one-year, multicenter, double-blind trial comparing placebo with 400 mg of acyclovir administered orally twice daily. Patients with episodes during the study were offered 200 mg of acyclovir administered orally five times daily for five days; this allowed comparison of suppressive and episodic treatment. After one year, 227 (44%) of 519 patients receiving suppressive treatment and seven (2%) of 431 receiving place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…While effective, this approach requires chronic daily dosing to maintain inhibition of the virus, demands good compliance, and is expensive (14,15,17,18,19). There is no posttreatment efficacy; discontinuation of suppressive treatment results in reversion to the pretreatment recurrence rate (6,23).…”
mentioning
confidence: 99%
“…While effective, this approach requires chronic daily dosing to maintain inhibition of the virus, demands good compliance, and is expensive (14,15,17,18,19). There is no posttreatment efficacy; discontinuation of suppressive treatment results in reversion to the pretreatment recurrence rate (6,23).…”
mentioning
confidence: 99%
“…This study also found that !10% of persons seropositive for HSV-2 reported a history of genital lesions [4]. Antiviral drug therapy shortens the severity and duration of lesions and reduces recurrences [5,6]. However, antiviral drug therapy is not applicable to prophylaxis and, although it is effective for the treatment of asymptomatic disease [7], its need may go unrecognized in this population, exacerbating the spread of disease.…”
mentioning
confidence: 99%
“…The efficacy of acyclovir for the treatment and suppression of anogenital herpes simplex virus (HSV) infections has been established in placebo-controlled trials (4,5,7). Despite estimates of the prevalence of acyclovir-resistant mutants within mucocutaneous herpetic lesions which range from 0 to 6.2% in untreated immunocompetent patients (1,3), cutaneous healing has generally been unimpeded in these hosts.…”
mentioning
confidence: 99%